Impact of Financial Performance on Financial Distress Banking Sectors Listed on The Indonesia Stock Exchange (IDX) In 2019 -2024 - Ratri Manohara Srikaya; Kartika Hendra Titisari; Sudarwati Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of financial performance on Financial Distress in banking sector companies listed on the Indonesia Stock Exchange for the period 2019–2024. The independent variables used are Return on Assets (ROA), Debt Ratio (DR), Operating Expenses to Operating Income (BOPO), Non-Performing Loans (NPL), and Capital Adequacy Ratio (CAR). The dependent variable is measured using the Zmijewski model. This study uses a quantitative approach with multiple linear regression methods. The sampling technique uses purposive sampling so that 13 conventional commercial banks are obtained as research samples with a total of 67 observations after outlier testing. The results show that partially ROA, DR, and CAR have a significant effect on Financial Distress. ROA has a negative effect on Financial Distress, which indicates that increasing profitability can reduce the possibility of financial distress. DR has a positive effect on Financial Distress, which indicates that increasing the proportion of liabilities to assets increases the risk of financial distress. CAR also has a significant effect on Financial Distress, which emphasizes the importance of capital adequacy in maintaining banking stability. Meanwhile, BOPO and NPL did not significantly influence financial distress. Simultaneously, all independent variables did not significantly influence financial distress. The adjusted R Square value of 0.080 indicates that the research model can only explain 8% of the variation in financial distress, with the remainder influenced by factors outside the model.